Influence of dual-cure and self-cure abutment cements for crown implants on human gingival fibroblasts biological properties - Guerrero-Gironés, Julia; López-García, Sergio; Pecci-Lloret, Miguel R.; Pecci-Lloret, María P.; García-Bernal, David (Annals of anatomy, 2022)
•Dual cure and self-cure abutment cements exhibited different biological effects.•Type of curing is not a determining factor in cytotoxicity, being the composition of the materials more important.•Multilink Hybrid Abutment obtained better in vitro biocompatibility, being the most eligible cement for crown implant. To analyze the biological effects of the cements Relyx Unicem 2, Panavia V5, Multilink Hybrid Abutment and SoloCem on human gingival fibroblast cells (HGFs). HGFs were exposed to different eluates (n = 40) of the studied resin-based cements. Their cytotoxic effects and influence on cell migration were assessed using MTT and wound-healing assays, respectively. Level of HGF attachment, cell morphology and F-actin cytoskeleton content after exposition to the different eluates were analyzed by scanning electron microscopy (SEM) and confocal microscopy analysis, respectively. The levels of intracellular reactive oxygen species (ROS) produced by the eluates of the different cements were also determined by flow cytometry. Data were analyzed by one-way analysis of variance (ANOVA) followed by Tukey´s test. Eluates of SoloCem significantly reduces the viability of HGFs (69% reduction compared to control at 48 h). Cell migration of HGFs in presence of undiluted SoloCem eluates was significantly lower than in the control (88% open wound area at 24 h). Contrarily, migration speed with Multilynk eluates was similar to that of the control group at all periods of time and all dilutions studied. SEM analysis showed very few cells in SoloCem group, and a moderate cell growth in Multilink, Panavia and Relyx groups were detected. Finally, ROS levels detected in HGFs treated with the more concentrated SoloCem and Relyx dilutions were significantly enhanced compared with that in the control cells or the other groups (44% and 11% ROS positive cells, respectively). The results obtained in the present work suggest that Multilink hybrid abutment has better biological properties and lower cytotoxicity for cementing implant crowns on abutments.